Synthesis of Size‐Controllable NiCo2S4 Hollow Nanospheres Toward Enhanced Electrochemical Performance. Issue 3 (12th September 2020) - Zhang, Lei; Zhang, Haitao; Chu, Xiang; Liu, Fangyan; Guo, Chunsheng; Yang, Weiqing
Abstract : Although the synthesis of novel nanostructured metal sulfides has been well established, further size‐controllable optimization is still valuable to enhance their performance for various applications. Herein, a self‐template method to size‐controllably synthesize the hollow NiCo2 S4 nanospheres is reported. Uniformly monodisperse NiCo precursors with diameter widely ranging from 97 to 550 nm are controllably synthesized and subsequently transformed into hollow NiCo2 S4 nanospheres through in situ sulfidation. Smaller nanoparticles' diameter results in the hollow NiCo2 S4 nanospheres larger surface area and thinner shell thickness and hence provides much more electrochemical active sites as well as facilitate the ion and electron transfer. Consequently, the hollow NiCo2 S4 nanospheres—used as the electrode materials in supercapacitors—achieve 19% enhancement of specific capacity from 484.8 to 575.1 C g −1 through lowering the 42.5% diameter of hollow NiCo2 S4 nanospheres from 407 to 234 nm. Moreover, the hollow NiCo2 S4 nanospheres with 234 nm diameter exhibit superior rate capacity indicated by 49% capacity retention from 1 to 50 A g −1 and excellent cycling stability (77% after 2000 cycles). Furthermore, this method is a potentially general strategy in the size‐controllable synthesis of the metal sulfides hollow nanostructures and results in the remarkable electrochemical applications. Abstract : A potentially general strategy to size‐controllably synthesize the nickel–cobalt sulfide hollow nanomaterials based on self‐template method is proposed. The increased electrochemical sites and shortened ion and electron path significantly improve the electrochemical performance.